Metabolomics coupled with integrated approaches reveal the therapeutic effects of higenamine combined with [6]-gingerol on doxorubicin-induced chronic heart failure in rats - Jianxia Wen; Xiao Ma; Ming Niu; Junjie Hao; Ying Huang; Ruilin Wang; Ruisheng Li; Jian Wang; Yanling Zhao (BMC, 2020)
Abstract Background This study was aimed to investigate the therapeutic effects and potential mechanism of higenamine combined with [6]-gingerol (HG/[6]-GR) against doxorubicin (DOX)-induced chronic heart failure (CHF) in rats. Materials and methods Therapeutic effects of HG/[6]-GR on hemodynamics indices, serum biochemical indicators, histopathology and TUNEL staining of rats were assessed. Moreover, a UHPLC-Q-TOF/MS-based serum metabolic approach was performed to identify the metabolites and possible pathways of HG/[6]-GR on DOX-induced CHF. Results HG/[6]-GR had effects on regulating hemodynamic indices, alleviating serum biochemical indicators, improving the pathological characteristics of heart tissue and reducing the apoptosis of myocardial cells. Serum metabolisms analyses indicated that the therapeutic effects of HG and [6]-GR were mainly associated with the regulation of eight metabolites, including acetylphosphate, 3-Carboxy-1-hydroxypropylthiamine diphosphate, coenzyme A, palmitic acid, PE(O-18:1(1Z)/20:4(5Z,8Z,11Z,14Z)), oleic acid, lysoPC(18:1(9Z)), and PC(16:0/16:0). Pathway analysis showed that HG/[6]-GR on CHF treatment was related to twelve pathways, including glycerophospholipid metabolism, fatty acid metabolism, pantothenate and CoA biosynthesis, citrate cycle (TCA cycle), pyruvate metabolism, and arachidonic acid metabolism. Serum metabolites and metabolic pathways regulated by HG/[6]-GR appear to be related to energy metabolism. Conclusion Multivariate statistical analysis has provided new insights for understanding CHF and investigating the therapeutic effects and mechanisms of HG/[6]-GR, which influencing the metabolites and pathways related to energy metabolism pathway.